Benefits of Exercise Training for Children and Adolescents Undergoing Cancer Treatment: Results From the Randomized Controlled MUCKI Trial - Sandra Stössel; Marie A. Neu; Arthur Wingerter; Wilhelm Bloch; Philipp Zimmer; Claudia Paret; Khalifa El Malki; Freerk T. Baumann; Alexandra Russo; Nicole Henninger; Nadine Lehmann; Henrike Otto; et al. (Frontiers Media S.A., 2020)
Objective: In cancer patients, the impairment in muscle function is a frequently observed phenomenon. However, comprehensive evaluation of the effect of exercise training on muscle function in childhood cancer patients (CCPs) is sparse and therefore investigated in the MUCKI trial.Study Design: In the randomized controlled MUCKI trial, CCPs during intensive cancer treatment and aged 4-18 years were recruited. Eligible patients were enrolled soon after diagnosis as long as they were physically and mentally able to participate in exercise testing and training. Patients of the exercise group (n = 16) participated in average 2.7 ± 1.2 times per week in a combined resistance and endurance training with moderate exercise intensity, for a time period of 8.0 ± 2.1 weeks, while patients of the control group (n = 17) received usual care. Leg strength was evaluated as the primary endpoint. Secondary endpoints were 6-min walk performance, arm strength, body composition, fatigue, and health-related quality of life.Results: Comparisons of pre- and post-intervention results were evaluated by baseline and stratification criteria adjusted analysis and showed positive effects for the exercise group regarding leg strength [F(1, 20) = 5.733; p = 0.027*; ηp2 = 0.223], walking performance [F(1, 25) = 4.270; p = 0.049*; ηp2 = 0.146], fatigue [F(1, 13) = 8.353; p = 0.013*; ηp2 = 0.391], self-esteem [F(1, 6) = 6.823; p = 0.040*; ηp2 = 0.532], and self-reported strength and endurance capacity [F(1, 6) = 6.273; p = 0.046*; ηp2 = 0.511]. No significant differences were found for the other parameters.Conclusion: Within one of the first randomized controlled trials, the present study provides evidence for a positive effect of combined training in CCPs during intensive cancer treatment. Further research is needed to confirm these results and to evaluate their clinical impact.Clinical Trial Registration Number: NCT02612025.